Analysis of the possibility of using R718 for a heat pump of a heating system based on a liquid-vapor ejector - Sharapov, Serhii; Husiev, Danylo; Panchenko, Vitalii; Kozin, Viktor; Baha, Vadym (Eastern-European Journal of Enterprise Technologies, 2020)
The study explores the possibility of using water (R718) as a refrigerant for a heat pump installation of a heating system. This unit is a vapor compression heat pump with a regenerative heat exchanger in which the vacuum unit based on a liquid-vapor ejector is used instead of a scroll refrigeration compressor. The working process of such an apparatus is based on implementing a fundamentally new cycle that does not require the supply of working steam from the outside. Instead, steam is generated inside the vacuum unit. The article describes the proposed installation and its differences from the traditional one, both in terms of circuit solutions and in terms of the operating cycle. A thermodynamic calculation was performed for the proposed installation with R718 as the working medium and the traditional heat pump systems operating on refrigerants R142b, R254fa, and R410a. As a result of the calculation, the parameters of all the devices included in these schemes were obtained, and the conversion factors of the cycles were determined. To assess the feasibility of using R718 as a working substance and replacing the scroll refrigeration compressor with a liquid-vapor ejector, an exergy analysis was performed. This made it possible to fairly accurately determine the effectiveness of each circuit, since it implemented the possibility of comparing systems using several types of energy (for example, electrical and thermal). As a result, the values of exergetic efficiency of traditional and proposed schemes were obtained. The final stage of the study was the performance of a thermoeconomic analysis. The estimated cost was determined for a unit of heat quantity per ton of the product and per unit of the heated area obtained in a unit with the working substance R718 and traditional installations with the working substances R142b, R254fa, and R410a